Research on wireless power transfer technology of electric vehicles based on CPT (LC compensation and LCLC compensation) - Zhang, Fan (Nanyang Technological University, 2020)
This thesis first summarizes the development history and current status of wireless power transmission technology, then focuses on the introduction of the electric field coupled wireless power transmission system structure and basic working principle, and analyzes its characteristics compared with the magnetic field coupling method and analyzes this corresponding advantage. In addition, the working principles and mathematical models of IPT and CPT wireless energy transmission technologies are introduced respectively. On the basis of comparing the performance of IPT and CPT technologies, the CPT systems using doubled LC compensation circuits and doubled LCLC compensation circuits are compared, and the electric field coupling is also pointed out. The key issues that need to be studied and solved are considered as well as the key factors to achieve efficient electric field coupled wireless energy transmission. The preliminary experimental test results and simulations are given. Finally, the development of electric field coupled wireless energy transmission is prospected.